Peran Pendidikan Pancasila dalam Membangun Karakter dan Kesadaran Sosial Peserta Didik di SMP Negeri 11 Palembang - Septi Rotari; Mita Purnama; Citra Lidiawati; Nanang Jayani; Hikma Damayanti (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2026)
The purpose of this study is to determine the role of Pancasila education in building character and social awareness of students at SMP Negeri 11 Palembang. This study uses a descriptive qualitative method. Data collection techniques by means of interviews, observation and documentation. The results of the implementation of the study found that the role of Pancasila education in building character and social awareness of students at SMP Negeri 11 Palembang, it was found that all students from SMP Negeri 11 Palembang through Pancasila education subjects already have good character values ​​and also good social awareness in the school environment and also the community this is seen in the application reflected in Pancasila subjects and also activities such as extracurricular activities that shape the character and social awareness of students, as well as the existence of an attitude journal for each teacher, especially Pancasila education teachers, the journal contains events that occur in the learning process in the classroom towards student attitudes.